Obediência e revolução em Immanuel Kant : a derivação do dever jurídico a partir da ideia do direito - Og Almeida Campos (2023)
This thesis starts from a new interpretative matrix about the foundation of Kant's theory of right. This reinterpretation maintains that private law (mine and yours external), more precisely the right to property, is the basis on which public law will be built. This is only possible to be sustained insofar as the idea of right precedes the idea of strict duty from the state of nature. In this way, the law is recognized as being a moral faculty, namely, an authorization given by the reason that the arbitrators appropriate and enjoy what is external in an arbitrary way, at sweet will. Alongside the morally necessary (prohibited or obligated), the morally possible (permitted) concerns the acquired right to compose morality through the principle of universality. Since juridically the right precedes the duty, the external relations must be understood as conforming to the duty, as permitted, or licit. Thus, reconstituting the central steps of the idea of right from the state of nature will serve as an axis to verify that the legal duty derives from a synthetic a priori judgment, but that public law derives from an analytical judgment based on the omnilateral unification of arbitrations free. As the entire Kantian conceptual framework is based on the idea of right from the state of nature, therefore empirical elements do not constitute right. For this reason, the idea of the duty of obedience to the civil state is due to the idea of its constitution, just as the prohibition of revolution is due to the fact that the right does not derive from an unjust fact. The idea of revolution can only be reconstituted from the laws of nature, as a constitutively natural fact. To reconstitute this conceptual edifice, the first chapter deals with structuring the new interpretative matrix from its original authors, specifying the possibilities and challenges opened by it. In the second chapter, the fundamental arguments are reconstituted about the deduction of mine and your external in the Kantian doctrine of right, with the aim of confirming in the third chapter that the idea of public law is posited from the state of nature. Once verified that public law proceeds analytically from private law and can be known in idea from the state of nature, the ideas of obligation and revolution in the civil state are reconstituted in the fourth chapter. The correct ordering of the Kantian argument will confirm that the idea of obedience to the State is due to the idea of its constitution, because it expresses the omnilateral unification of the wills comprised by its power. Consequently, the idea of the duty of obedience to the State expresses the duty to refrain from harming the will of others. In turn, the idea of revolution is anchored in empirical elements, more precisely in the idea of imperfection of the State itself. However, the origin of the right does not result from facts. Therefore, the reconstitution of the idea of revolution must be done from its empirical nature, not from the idea of right, since they have different ontological statutes.